Predictors of extubation success: a population-based study of neonates below a gestational age of 26 weeks. Issue 1 (9th August 2022) - Ohnstad, Mari Oma; Stensvold, Hans Jørgen; Pripp, Are Hugo; Tvedt, Christine Raaen; Jelsness-Jørgensen, Lars-Petter; Astrup, Henriette; Eriksen, Beate Horsberg; Klingenberg, Claus; Mreihil, Khalaf; Pedersen, Tanja; Rettedal, Siren; Selberg, Terje Reidar; et al.
Abstract : Objective: The aim of the study was to investigate first extubation attempts among extremely premature (EP) infants and to explore factors that may increase the quality of clinical judgement of extubation readiness. Design and method: A population-based study was conducted to explore first extubation attempts for EP infants born before a gestational age (GA) of 26 weeks in Norway between 1 January 2013 and 31 December 2018. Eligible infants were identified via the Norwegian Neonatal Network database. The primary outcome was successful extubation, defined as no reintubation within 72 hours after extubation. Results: Among 482 eligible infants, 316 first extubation attempts were identified. Overall, 173 (55%) infants were successfully extubated, whereas the first attempt failed in 143 (45%) infants. A total of 261 (83%) infants were extubated from conventional ventilation (CV), and 55 (17%) infants were extubated from high-frequency oscillatory ventilation (HFOV). In extubation from CV, pre-extubation fraction of inspired oxygen (FiO2 ) ≤0.35, higher Apgar score, higher GA, female sex and higher postnatal age were important predictors of successful extubation. In extubation from HFOV, a pre-extubation FiO2 level ≤0.35 was a relevant predictor of successful extubation. Conclusions: The correct timing of extubation in EP infants is important. In this national cohort, 55% of the first extubation attempts were successful. Our results suggest that additional emphasis on oxygen requirement, sex and general condition at birth may further increase extubation success when clinicians are about to extubate EP infants for the first time.